Preface - Corte-Real, João (2012)
This special issue of Nonlinear Dynamics includes a selection of articles presented at the conference Nonlinear Dynamics of Electronic Systems (NDES, 2004) held at the University of E ́ vora, Portugal, 9–13 May 2004. The conference was the twelfth in a series of international conferences, which were initiated at Dresden in 1993. It brought together specialists in the mathematical, natural and engineering sciences to address new theoretical and practical results, novel analysis and design methods in nonlinear dynamic systems and circuits and to discuss open problems in nonlinear science.